2022
DOI: 10.1186/s13052-022-01313-7
|View full text |Cite
|
Sign up to set email alerts
|

Neurological vertigo in the emergency room in pediatric and adult age: systematic literature review and proposal for a diagnostic algorithm

Abstract: Neurological vertigo is a common symptom in children and adults presenting to the emergency department (ED) and its evaluation may be challenging, requiring often the intervention of different medical specialties. When vertigo is associated with other specific symptoms or signs, a differential diagnosis may be easier. Conversely, if the patient exhibits isolated vertigo, the diagnostic approach becomes complex and only through a detailed history, a complete physical examination and specific tests the clinician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 82 publications
(186 reference statements)
0
1
0
Order By: Relevance
“…These symptoms are momentary and completely disappear following delivery. Women who have MD during pregnancy often have episodic vertigo, variable sensorineural hearing loss, and roaring or hissing tinnitus [ 34 ].…”
Section: Reviewmentioning
confidence: 99%
“…These symptoms are momentary and completely disappear following delivery. Women who have MD during pregnancy often have episodic vertigo, variable sensorineural hearing loss, and roaring or hissing tinnitus [ 34 ].…”
Section: Reviewmentioning
confidence: 99%
“…Nevertheless, it is a common reason for emergency department presentation, both alone or associated with other symptoms. Pellegrino et al [174] reported on the etiopathology of neurological vertigo in childhood and adulthood, highlighting the characteristics which may lead clinicians to a proper diagnosis, and proposed a diagnostic algorithm to support the approach to patients with isolated vertigo, both in pediatric and adult age. The most common cause of isolated vertigo in the pediatric population is vestibular migraine, followed by benign paroxysmal vertigo in childhood.…”
Section: -Vertigomentioning
confidence: 99%
“…Također, mo guća je i pojava nistagmusa. 6 Dok epizode periferne vrtoglavice imaju tendenciju brzog prestanka, central na vrtoglavica često dolazi bez upozorenja i može tra jati dugo. Epizode su općenito mnogo intenzivnije od perifernih i često bolesnik ne može hodati i stajati bez pomoći.…”
Section: Razlike Između Periferne I Centralne Vrtoglaviceunclassified
“…Moždani udar, infekcija SŽSa ili trauma mogu uzrokovati ne samo akutnu ili subakutnu vrtoglavicu, već i dizartriju (nejasan govor), ataksiju (probleme s kretanjem), slabost i obamrlost/ trnce. 6 Centralna je etiologija najčešća u gotovo 70% uzroka vrtoglavice.…”
Section: Razlike Između Periferne I Centralne Vrtoglaviceunclassified
See 1 more Smart Citation